Brief (<4 hr) sleep episodes are insufficient for restoring performance in first-year resident physicians working overnight extended-duration work shifts. Issue 5 (22nd February 2019) - St Hilaire, Melissa A; Anderson, Clare; Anwar, Junnat; Sullivan, Jason P; Cade, Brian E; Flynn-Evans, Erin E; Czeisler, Charles A; Lockley, Steven W; ,
Abstract: Study Objectives: The Accreditation Council for Graduate Medical Education (ACGME) recently reinstated extended-duration (24–28 hr) work shifts (EDWS) for postgraduate year 1 (PGY-1) resident physicians. This study examined the relationship between overnight sleep duration during EDWS and subsequent "post-call" performance in PGY-1 resident physicians. Methods: Thirty-four PGY-1 resident physicians (23 males; 24–32 years) were studied between 2002 and 2004 during 3-week Q3 "on-call" rotation schedules in the Medical and Cardiac Intensive Care Units at Brigham and Women's Hospital in Boston. Daily sleep logs (validated by ambulatory polysomnography) were collected and the 10 min psychomotor vigilance task (PVT) was administered every 6 hr during each EDWS. Generalized estimating equations were used to examine the relationship between overnight sleep duration and PVT performance "post-call" (0500–1900 hr). Postcall performance during EDWS was compared with sessions matched for time-of-day and weeks-into-schedule in the same resident physician during an intervention schedule that eliminated EDWS. Results: Resident physicians obtained an average of 1.6 ± 1.5 hr cumulative sleep overnight during EDWS (<4 hr on 92% of nights). PVT attentional failures were significantly reduced only after >4 hr sleep ( p = 0.027 versus no sleep). Despite this apparent improvement, the odds of incurring >1 attentional failure were 2.72 times higher during postcall following >4 hr sleep compared with matched sessions during non-EDWS. Conclusions: Even with >4 hr sleep overnight (8% of EDWS), performance remained significantly impaired. These findings suggest that even "strategic napping, " a recommendation recently removed from ACGME guidelines, is insufficient to mitigate severe performance impairment introduced by extending duty beyond 16 hr.